The paradox of spironolactone: A heart failure treatment with potentially harmful effects - Muhammad Roshan; Muhammad Ahmad Nadeem; Sahar Imran Khalfay (Journal of the Pakistan Medical Association, 2024)
Madam, Heart failure (HF) is a multifaceted clinical syndrome arising from a functional or structural cardiac condition that hampers the adequate filling or expulsion of blood into the systemic circulation. It is estimated that heart failure affects around 26 million people globally and significantly adds to healthcare expenditures on a worldwide scale1. Furthermore, in 2016, approximately 16 percent of deaths in Pakistan were due to heart related disorders. This number grew to 29 percent in 20222. HF can greatly diminish the functional capability of a patient and heighten the risk of mortality. Therefore, it is essential to accurately diagnose and proficiently manage this condition to improve the quality of life of the patient. Spironolactone, the first mineralocorticoid receptor antagonist (MRA) to be developed, is prescribed for the management of hypertension, primary hyperaldosteronism, and peripheral oedema linked to cardiac failure3. When HF occurs and cardiac output decreases, it stimulates the renin-angiotensin-aldosterone system (RAAS) which in turn causes salt and water reabsorption and thus increases venous return to the heart which further contributes to congestive heart failure and heart fails to pump the additional fluid and pooling occurs. Here MRAs are very affective as they inhibit the function of aldosterone and hence fluid retention does not occur. Unfortunately, the beneficial effects of spironolactone do not occur without substantial adverse effects. Firstly, spironolactone is associated with sexual adverse events due to its affinity for androgen and progesterone receptors. There have been reports of male patients experiencing gynecomastia and breast pain. Secondly, spironolactone has been classified as potassium sparing diuretic hence hyperkalemia (defined as serum K+ > 5.5 mEq/L) is a common side effect3. Hyperkalemia can manifest as muscle weakness or paralysis, metabolic acidosis, cardiac conduction abnormalities, and life-threatening cardiac arrhythmias4. These cardiac arrythmias can have serious consequences, including cardiac arrest and stroke. In conclusion heart failure, if not treated immediately, can be fatal. Spironolactone is a drug used for management of heart failure; however, it has some detrimental effects on the cardiovascular system such as development of serious cardiac arrythmias. Hyperkalemia, due to potassium sparing nature of MRAs, is the primary cause of these life-threatening effects thus it is recommended to assess serum potassium levels and renal function of a patient with heart failure before prescribing spironolactone. Moreover, patients who are being treated with spironolactone should be periodically monitored to prevent any casualty.